GAMBARAN TINGKAT STRES YANG DIALAMI PARA PERAWAT DALAM MERAWAT PASIEN COVID-19 DI RSUD GAMBIRAN KEDIRI - Slamet Jayadi; Katmini (STIKes Maharani Malang, 2022)
Introduction: Covid-19 is a new emerging disease, the large number of incidences and death rates due to Covid-19 causes psychological factors (stress) both to the community and also to health workers. The focus of this research is to describe the causes and levels of stress experienced by nurses who treat Covid-19 at Gambiran Hospital. Method: This study uses a qualitative research design. The sample in this study were some of the nurses and midwives who served in the isolation room and the emergency room at Gambiran Hospital, Kediri, as many as 6 participant informants and 1 triangulation informant. The sampling technique used is purposive sampling. Data collection using in-depth interviews. Result and analysis: The results showed that nurses' stress was influenced by 2 themes, namely the causes of stress experienced by nurses who treated Covid-19 at Gambiran Hospital, most of the patients treated in the covid room were in the moderate to severe category, the stress level of nurses. Discussion: Most expressed feelings of anxiety, worry, stress and anxiety when assigned to the covid isolation room The large number of incidences and death rates due to COVID-19 causes stress to nurses caring for Covid-19 patients, including the overload of Covid-19 patients, shortage of medical personnel and supporting infrastructure, increasing workload, lack of rest time and nurses who are afraid of contracting Covid-19. Keywords: stress level, nurses, caring for covid 19 patients